2020
DOI: 10.1108/jmd-05-2019-0180
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of organizational commitment in cooperatives in Ecuador

Abstract: PurposeThe objective of this research is to analyse the affective organizational commitment in cooperatives in Ecuador. This was done by adapting and testing a measurement scale based on the one-dimensional model proposed by Porter.Design/methodology/approachField work was carried out, with a structured questionnaire being given to a significant sample of workers in Ecuadorian cooperatives (2,499 employees and heads of department). The scale was adapted through a structural equation model.FindingsThe results s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 55 publications
0
11
0
2
Order By: Relevance
“…This enhanced understanding of the business by those members seems to increase the motivation, engagement, and empathy toward other members in the same representative positions. Previous research had already shown that involvement in strategic management ( Hidalgo-Fernández et al, 2020 ), decentralization and participative decision-making ( Agirre et al, 2014 ) all have a positive relationship with workers’ organizational commitment in worker cooperatives. However, our research suggests that one factor that could explain such positive relationship is the intensive learning process that takes place as worker-members actively participate in management, for instance in the governing bodies of the cooperative.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This enhanced understanding of the business by those members seems to increase the motivation, engagement, and empathy toward other members in the same representative positions. Previous research had already shown that involvement in strategic management ( Hidalgo-Fernández et al, 2020 ), decentralization and participative decision-making ( Agirre et al, 2014 ) all have a positive relationship with workers’ organizational commitment in worker cooperatives. However, our research suggests that one factor that could explain such positive relationship is the intensive learning process that takes place as worker-members actively participate in management, for instance in the governing bodies of the cooperative.…”
Section: Discussionmentioning
confidence: 99%
“…A study of French agricultural cooperatives concluded that members participate in the governance of their cooperative when they are attached to it affectively and trust the directors ( Barraud-Didier et al, 2012 ). Another study in cooperatives in Ecuador found that certain variables related to job position such as higher salary levels, involvement in strategic management (specifically being an executive), or temporary contracts all had a significant and positive relationship with organizational commitment ( Hidalgo-Fernández et al, 2020 ). In a comparative analysis between worker cooperatives and capitalist firms in South Korea, Park (2018) found that the increase in job demands and workloads in cooperatives did not seem to reduce the organizational commitment of their members, most likely because they are provided with greater autonomy, organizational support, decision-making participation, and social support as compared to their capitalist counterparts.…”
Section: Organizational Commitment and Organizational Democracymentioning
confidence: 99%
“…Journal of Co-operative Organization and Management [27] Project-based governance framework for an agri-food cooperative Sustainability [28] Analysis of organizational commitment in cooperatives in Ecuador Journal of Management Development [29] Cooperativismo, políticas públicas y organizaciones sociales: Conflictividad en cooperativas promovidas por el Estado en Argentina Psicoperspectivas [30] One for All and All for One? A New Generation of Co-operatives Emerges Scandinavian Journal of Management Long Range Planning [31] Navigating dynamic contexts: African cooperatives as institutional bricoleurs International Journal of Agricultural Sustainability [32] El nivel de conocimiento y la reputación social de las empresas cooperativas.…”
Section: Authors/publication Yearmentioning
confidence: 99%
“…Organizational commitment was measured using the Organizational Commitment Questionnaire (Mowday et al, 1979), which consists of 15 statements (see appendix 2). It is an instrument developed in 1970 by Porter and Smith (Kanning & Hill, 2013) and it is one of the most frequently used instruments for measuring organizational commitment (Hidalgo-Fernández, Mero, Alcivar & Santa Cruz, 2020;Bar-Haim, 2019;Kanning & Hill, 2013;Hartmann & Bambacas, 2000). Empirical research has confirmed that it is an instrument that has high internal consistency and validity (Hidalgo-Fernández et al, 2020;Kanning & Hill, 2013;Yousef, 2003;Lam, 1998).…”
Section: Measurementmentioning
confidence: 99%